Self as Method Thinking Through China and the World - Xiang, Biao; Wu, Qi (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
Despite China's rise to the status of global power, many Chinese youths are anxious about their personal future, in large measure because the rapid changes have left them feeling adrift. This book, available in open access, provides a manifesto of intellectual activism that counsels China's young people to think by themselves and for themselves. Consisting of three conversations between Xiang Biao, a social anthropologist, and Wu Qi, a rising journalist, the book probes how China has reached its current stage and how young people can make changes. The conversations touch on issues of mobility, education, family, relations between the self and the authority, centers and margins, China, and the world. The Chinese version was named the "most impactful book of 2021" by Douban, China's premier website for rating books, films, and music. The English version is translated by David Ownby, who also penned an introduction. Xiang Biao is a social anthropologist who was born and educated in China and now the director of the Max Planck Institute for Social Anthropology. Wu Qi is a journalist and an editor of 'One Way Street,' a Chinese literary magazine. David Ownby is a full professor, Department of History, Centre d'études de l'Asie de l'Est, Université de Montréal.